Effect of combinations of rumen-protected methionine plus rumen-protected lysine on performance of finishing steers - G. Goldy; Jack G. Riley; Ronald V. Pope (Kansas Agricultural Experiment Station Research Reports, 1986)
Feed efficiency for finishing steers was significantly improved (7.4%) when rumen-protected methionine and lysine were added to a finishing ration.
Keywords: Cattlemen' s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Methionine; Lysine; Rumen; Finishing steers